PEMBINAAN PRESTASI EKSTRAKURIKULER OLAHRAGA DI SMA KARANGTURI KOTA SEMARANG (Department of Physical Education, Sport, Health and Recreation, 2013)
Coaching is a factor that determines the performance improvement, one of them is extracurricular sports.Achievements will be achieved if development is done intensively, quality, and quality (Tohar, 2002). One ofthe schools that have their sporting achievements in Semarang is SMA Karangturi. Therefore, researchers areinterested in knowing how the coaching sports extracurricular achievement in SMA Karangturi Semarang.This study aims to determine sports coaching extracurricular achievement in SMA Karangturi Semarang2012/2013. This research used a qualitative approach. Respondents in this research is the head master of SMAKarangturi Semarang, gym teacher of SMA Karangturi, and sports extracurricular coaches of SMAKarangturi Semarang. Informants are high school students who take the Semarang Karangturi extracurricularsports activities. Techniques of data collection using interviews and documentation techniques. Examination ofthe validity of the data using triangulation techniques. Analysis using qualitative data analysis techniquesderived from Miles and Huberman. Consists of data collection, data reduction, data display, and conclusiondrawing or verification.Based on the results of research conducted it can be concluded that the development ofsports extracurricular achievementsin SMA Karangturi Semarang has the advantage that (1) the completenessof facilities and infrastructure supporting sports development activities, (2) an intensive training program, (3) agood management of the organization, and (4 ) scholarships and hostel facilities for athletes.